RUPTURE AND GLITCH IN PLEASURE: EXPLORING EROTIC ROLE PLAY IN VIRTUAL REALITY - Bahar, Ilker (AoIR Selected Papers of Internet Research, 2026)
Sex is not a seamless experience. It involves moments of rupture, disconnection and failure. Even more so when it is digitally mediated. Sexting, phone sex, or long-distance intimacy via cameras and tele-dildonics all intertwine pleasure with the quirks of technology—unpredictable internet connections, lag, latency, glitches. Yet in mainstream depictions, sex is stripped of these interruptions and is portrayed as an effortless choreography: bodies meeting flawlessly, fluids exchanged with precision at the right moment, the penis always erect… Today, in social VR platforms such as VRChat, thousands of users put on their VR headsets and body trackers to engage in what is called “erotic role play” through 3D avatars. They don different avatars ranging in aesthetics from the anime and animals to objects like toothbrushes. Drawing on the author’s digital ethnography in VRChat, this paper will examine how users negotiate desire, intimacy and sex during these immersive encounters. Central to this examination will be the moments of rupture, disconnection and glitches that users often experience in their avatarial embodiments. For example, when tracking fails, the user might end up having their avatarial body parts dislocated or see their partner slower than usual in case of latency. Building on queer theory and glitch feminism (Russell, 2020; Sundén, 2015), this paper will argue that these ruptures might subvert cis-heteronormative and ableist frameworks around sex and intimacy. By embracing imperfection and subverting normative assumptions around pleasure, these disruptions can open possibilities for reimagining intimacy in playful, experimental, and non-normative ways.